'Under the Gallic Spell': Boston's Embrace of Gabriel Fauré, 1892–1924. Issue 2 (12th August 2022) - de Savage, Heather
Abstract : French influence on American twentieth-century music has long been central to historical narratives, particularly in relation to Nadia Boulanger and her pupils from the 1920s onward. Yet the much earlier impact of Gabriel Fauré (1845–1924), Boulanger's own teacher, has been largely ignored. While most American audiences around the turn of the century were largely unfamiliar with Fauré, Boston embraced his music enthusiastically. By the 1890s, a growing Francophile aesthetic reflected in the city's musical life encouraged performances of French repertoire, and a remarkable number of Fauré's compositions were introduced, some heard frequently enough to become well known to local audiences. Many of Boston's most influential critics, educators, performers and patrons admired Fauré and advocated for him as a representative modern French composer. That his music was so warmly welcomed in Boston at the end of the nineteenth century without any overt self-promotion by the composer has not been widely known until now. Although Fauré never visited the United States, his music found a home away from home in Boston, both while he was still living and well beyond.